Studies on Japanese B Encephalitis Virus Vaccines from Tissue Culture: XI. Immune Mechanism and Evaluation of the Mouse Challenge Potency Test - Singh, Balwant (1971)
A study was carried out to evaluate the reliability of and to determine the mechanism involved in an antigen extinction mouse intraperitoneal (ip) challenge test for potency of a cell culture vaccine for Japanese B encephalitis, a modification of a test originated by Sabin for a mouse brain vaccine. Some comparisons were made with the official Japanese test using an intracerebral (ic) challenge after a more prolonged immunization procedure. The Japanese method of using a lyophilized reference vaccine with each test was also employed. It was found that the ip and the ic test appeared to show similar relative differences between lots. The ip test was more quickly and readily performed, gave reasonably consistent results on repetition, and, when used with a suitable reference vaccine, gave promise of being an entirely suitable and reliable test. Immunization by the intramuscular route rather than by the regular ip route appeared to offer no advantage and was less consistent in responses shown. Neutralizing antibody responses of the mice in the standard procedure were very quick to appear, about 4 days after the first dose of vaccine and had a peak titer about the seventh day, the time of challenge. This titer fell quickly unless challenge occurred. The antibody was heat stable, but it was readily inactivated by 2-mercaptoethanol (2-ME). Not until the 11th or 15th day did a small amount of immunoglobulin G appear. Challenge on day 7 significantly increased titers, but this antibody was also mostly inactivated by 2-ME. Interferon did not appear to play any significant role in the protection shown by the mice.